Formação de professores da educação básica: análise comparativa entre a BNC-Formação e o modelo francês - Carvalheira, Eliana Mariano (2022)
This thesis studied the foundation school teacher preparation in Brazil, based on the analysis of the Resolution CNE/CP N°2/2019, which defined the National Curriculum Guidelines for the Initial Preparation of Foundation Teachers (BNC-Formation), based on the French teacher preparation model. In France, since 2019, the teacher preparation is offered in the INSPÉ, masters level, following the Law number 2019-791 “for a reliable school”. The importance of the discussion about the teacher preparation comes from the significant transformation in the political, economical, and social scenarios, influenced by neoliberalism and in which education, as a social phenomenon, was not exempt of changes, being affected by several reforms, many influenced by international organizations. In this context, the objective of this research is to identify the elements from the French teacher preparation that can contribute to a reflection about the foundation school teacher preparation in Brazil. A qualitative approach was adopted, including the documental research procedures. For the data and interpretation analysis was used the content analysis technic. Based on the obtained results, it was concluded that Brazil and France are influenced by neoliberal teacher preparation politics. However, even considering the different realities between the two countries, it was also possible to conclude that some elements of the French teacher preparation can contribute to the teacher preparation in Brazil: the relationship between the theory and the practice in the trainee program and in the University; the preparation for research; the school as the privileged place for preparation; the teacher’s role in the school. Because of that, it was highlighted that it is not possible to consider educational politics apart from social and economical politics, as they are part of the same group of actions that represent the current structures and power relationships. It is possible to state that the reflection about the French teacher preparation model amplifies theoretically the knowledge about the teacher formation structure and organization in Brazil and in France, using a comparative approach. Furthermore, the proposal of this thesis can provoke managers, coordinators, and teacher preparation course developers, leading to ways that can contribute to changes(AU)